Hygrothermal effects on the shear properties of carbon fiber/epoxy composites - Botelho, E. C.; Pardini, L. C.; Rezende, M. C. (Springer, 2006)
The environmental factors, such as humidity and temperature, can limit the applications of composites by deteriorating the mechanical properties over a period of time. Environmental factors play an important role during the manufacture step and during composite's life cycle. The degradation of composites due to environmental effects is mainly caused by chemical and/or physical damages in the polymer matrix, loss of adhesion at the fiber/matrix interface, and/or reduction of fiber strength and stiffness. Composite's degradation can be measure by shear tests because shear failure is a matrix dominated property. In this work, the influence of moisture in shear properties of carbon fiber/epoxy composites ( laminates [0/0](s) and [0/90](s)) have been investigated. The interlaminar shear strength (ILSS) was measured by using the short beam shear test, and Iosipescu shear strength and modulus (G(12)) have been determinated by using the Iosipescu test. Results for laminates [0/0](s) and [0/90](s), after hygrothermal conditioning, exhibited a reduction of 21% and 18% on the interlaminar shear strenght, respectively, when compared to the unconditioned samples. Shear modulus follows the same trend. A reduction of 14.1 and 17.6% was found for [0/0](s) and [0/90](s), respectively, when compared to the unconditioned samples. Microstructural observations of the fracture surfaces by optical and scanning electron microscopies showed typical damage mechanisms for laminates [0/0](s) and [0/90](s).